TECHNICAL-ECONOMIC ANALYSIS, CALCULATION AND JUSTIFICATION OF FRESHWATER PRODUCTION IN THE REPUBLIC OF UZBEKISTAN - Rakhimov, Nurbek (Innovatsion texnologiyalar, 2024)
Despite the presence of large rivers such as Amudarya and Syrdarya, water distribution problems in Uzbekistan are aggravated by the large demand for water from agriculture and the drying up of the Aral Sea. The shift to growing water-intensive crops further depletes available resources. These challenges require innovative approaches to freshwater production that include advanced technologies and economic feasibility assessments. A costing model estimates the capital and operating costs of various water production technologies, the breakeven cost of produced water (LCOW). Several technologies were calculated and compared to determine the most cost-effective LCOW options. Solar radiation is high in Karshi, Bukhara and Termez. For this reason, a larger part of the annual solar energy falls on these regions. Given these data, LCOW does not vary significantly across regions, with all values falling between $0.10 and $0.14 per cubic meter. A parallel analysis was conducted in the cities of Tashkent, Samarkand, Karshi, Andijan and Namangan in the comprehensive assessment of the cost of water production in the territory of Uzbekistan, and small differences in the standardized cost of water were identified. LCOW was estimated at $0.10 to $0.14 per cubic meter.